2013
DOI: 10.2478/s13382-013-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to electromagnetic field radiation (EMFR) generated by activated mobile phones on fasting blood glucose

Abstract: Objective: Extensive use of mobile phones has been accompanied by a common public debate about possible adverse effects on human health. No study has been published so far to establish any association between the fastest growing innovation of mobile phone and fasting blood glucose. The aim was to determine the effects of exposure to electromagnetic field radiation generated by mobile phones on fasting blood glucose in Wistar Albino rats. Materials and Methods: 40 Male Albino rats (Wistar Strain) were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Meo et al [ 25 ] determined the effects of exposure to RF-EMFR generated by mobile phones on fasting blood glucose in albino rats. The authors found that, Wister albino rats exposed to RF-EMF generated by mobile phone for more than 15 min a day for a maximum period of three months had significantly higher fasting blood glucose and serum insulin compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meo et al [ 25 ] determined the effects of exposure to RF-EMFR generated by mobile phones on fasting blood glucose in albino rats. The authors found that, Wister albino rats exposed to RF-EMF generated by mobile phone for more than 15 min a day for a maximum period of three months had significantly higher fasting blood glucose and serum insulin compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that, Wister albino rats exposed to RF-EMF generated by mobile phone for more than 15 min a day for a maximum period of three months had significantly higher fasting blood glucose and serum insulin compared to the control group. Meo et al [ 25 ] also reported that increase in fasting blood glucose was due to insulin resistance. In the present study, we found that students who were exposed to high RF-EMFR generated by MPBS had significantly higher HbA1c ( Table 1 ) and a higher prevalence of type 2 diabetes mellitus ( Table 2 ) than the students who were exposed to low RF-EMFR.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to the these findings, several studies have shown that pulsed electromagnetic field are effective in antihyperglycemia in diabetic rats (Jing et al, 2011; Mert et al, 2010). Moreover, it was determined that Wistar Albino rats exposed to RFR emitted from mobile phones (1800 MHz, GSM, 15 min/day for 3 months) had higher fasting blood glucose compared to the control group (Meo & Al Rubeaan, 2013). In addition, it was stated that exposure to electromagnetic pollution cause higher blood glucose levels and may contribute to diabetes mellitus (Havas, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is growing evidence that people and animals exposed to 900 MHz radiation present thyroid function and morphology alterations (Djeridane et al, 2008;Riccioni et al, 2004;Bergamaschi et al, 2004;Eskander et al, 2012;Hackney and Gulledge, 1994;Koyu et al, 2005;Shahryar et al, 2009). The effect of cellular phone use on fasting glucose is established in the literature (Meo and Al Rubeaan, 2013), while scarce data exist on insulin secretion or insulin resistance to cellular phone call response.…”
Section: Introductionmentioning
confidence: 99%